REVIEW OF THE ROOFING MATERIAL OF THE PURBALINGGA CATHOLIC CHURCH ON THE IMPACT OF SPACE HEAT - Yohanes Wahyu Dwi Yudono (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2019)
Starting from observing the roof of the Purbalingga Parish Catholic Church (which in this case serves as the crown of the building), every observer will be quickly attracted because it has a beautifulappearance. But beauty alone is not enough, there are at least 3 aspects according to Vitruvius that need tobe considered in terms of buildings, namely Function, Robustness, and beauty. The two aspects have atleast been fulfilled, leaving for the aspect of the function of the church building which is still questionable.The function of the building in question here concerns the beauty of the roof that does not functionoptimally in fending off solar radiation. The function of the roof as a building shield is to ward off heatradiation from the sun, so that the roof itself is demanded not to be an easy source of heat radiation whichforwards most of the heat radiation it receives from the sun into the space it is supposed to protect. This isrelated to the nature of heat conductivity of the roofing material used. High temperatures in buildings are not only caused by the shape of the building (construction ofroofs, walls, and floors of buildings), but are also caused by the use of materials and completion ofbuilding construction, each of which has heat resistance. Therefore it is necessary to find out how much thevalue of heat prisoners on the application of the Catholic church roof material in Purbalingga. From the observations it can be concluded that, in addition to the way of constructing the churchroof which causes air to gather on the top of the main roof, also found the coefficient of heat transfercoefficient of the church roof of 2.725 kcal / m2.jam0C. This means that the value of the heat transfercoefficient (K) of roof construction is greater than the requirement of 1.00 kcal / m2.jamC, thus the roofconstruction applied to the church does not meet the requirements for the interests of the ability of heatprisoners. Key Words: Roof Forms, How to Construct a Roof Frame, Heat Conductivity of Roofing Materials. ABSTRAKBermula dari mengamati Atap Gereja katolik Paroki Purbalingga (yang dalam hal ini berlaku sebagai mahkota bangunan), setiap pengamat akan cepat tertarik karena memiliki tampilan bentuk yangindah. Namun keindahan saja belum cukup, paling tidak ada 3 aspek menurut Vitruvius yang perludiperhatikan dalam hal bangunan, yaitu Fungsi, Kekokohan, dan keindahan. Dua aspek paling tidak sudahterpenuhi, tinggal untuk aspek fungsi bangunan gereja yang masih mungkin dipertanyakan. Fungsibangunan yang dipertanyakan disini menyangkut indahnya atap yang tidak berfungsi secara optimal dalammenangkis radiasi matahari. Fungsi atap sebagai perisai bangunan yaitu menangkal radiasi panas darimatahari, sehingga atap sendiri dituntut jangan mudah menjadi sumber radisi panas yang meneruskan sebagian besar radiasi panas yang diterimanya dari matahari ke dalam ruang yang semestinyadilindunginya.  Hal inilah yang berhubungan dengan sifat daya penghantaran panas dari bahan atap yangdipakainya. Temperatur yang tinggi dalam bangunan tidak hanya disebabkan oleh bentuk bangunan (konstruksiatap, dinding, dan lantai bangunan), namun juga disebabkan oleh penggunaan material dan penyelesaiaankonstruksi bangunan yang masing-masing memiliki tahanan kalor. Oleh karena itu perlu untuk mengetahuiberapa besar nilai tahanan kalor pada penerapan material atap gereja Katolik di Purbalingga tersebut. Dari hasil pengamatan dapat disimpulkan bahwa, selain cara berkonstruksi atap gereja yangmengakibatkan udara mengumpul pada bagian atas atap utama, juga ditemukan nilai koefisien perpindahankalor atap gereja sebesar 2,725 kcal / M2.jam0C.  Artinya nilai  koefisien perpindahan kalor (K) konstruksiatap lebih besar dari persyaratan yaitu 1,00 kcal / M2.jam0C, dengan demikian konstruksi atap yangditerapkan pada gereja tidak memenuhi persyaratan bagi kepentingan kemampuan tahanan kalor.Kata-kata Kunci :  Bentuk Atap, Cara Ber-Konstruksi Rangka Atap, Daya Hantar Panas MaterialAtap. 0